2014
DOI: 10.3109/01902148.2014.948231
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan aerosol inhalation alleviates lipopolysaccharide- induced pulmonary fibrosis in rats

Abstract: Our findings show that chitosan aerosol inhalation inhibits the expression of MMP-3 and TIMP-1, and ameliorates LPS-induced pulmonary remodeling and fibrosis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The histopathology of lung tissue sections in animals pre-treated with Ch-NPs showed a normal appearance. Our findings agreed with those of Zhou et al (2014) who suggested that chitosan exhibited potent antifibrotic activities by reducing fibroblast proliferation, decreasing extracellular matrix deposition and collagen synthesis levels. In addition, chitosan was shown to stimulate reepithelialization in experimental wounds ( Lee et al 2016a, b).…”
Section: Discussionsupporting
confidence: 93%
“…The histopathology of lung tissue sections in animals pre-treated with Ch-NPs showed a normal appearance. Our findings agreed with those of Zhou et al (2014) who suggested that chitosan exhibited potent antifibrotic activities by reducing fibroblast proliferation, decreasing extracellular matrix deposition and collagen synthesis levels. In addition, chitosan was shown to stimulate reepithelialization in experimental wounds ( Lee et al 2016a, b).…”
Section: Discussionsupporting
confidence: 93%
“…While fibrosis progression is characterised by extracellular matrix (ECM) accumulation and fibroblast proliferation, chitosan is known to inhibit the latter with potent effects on collagen synthesis and ECM production (4,15). TGF-β reportedly plays a crucial role in idiopathic PF and animal models of lung fibrosis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that chitosan decreases the levels of BUN and CRE and elevates the activities/levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) in an adenine-induced rat model of CRF [ 9 ]. Moreover, chitosan exerts potent anti-fibrosis activity by inhibiting tissue inhibitor of metalloproteinase-1 (TIMP-1) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%